Diversification of human plasmacytoid predendritic cells in response to a single stimulus - Alculumbre, Solana G.; Saint-André, Violaine; Di Domizio, Jeremy; Vargas, Pablo; Sirven, Philemon; Bost, Pierre; Maurin, Mathieu; Maiuri, Paolo; Wery, Maxime; Roman, Mabel San; Savey, Léa; Touzot, Maxime; et al. (Nature immunology, 2018)
Innate immune cells adjust to microbial and inflammatory stimuli through a process termed environmental plasticity, which links a given individual stimulus to a unique activated state. Here, we report that activation of human plasmacytoid predendritic cells (pDCs) with a single microbial or cytokine stimulus triggers cell diversification into three stable subpopulations (P1–P3). P1-pDCs (PD-L1 + CD80 – ) displayed a plasmacytoid morphology and specialization for type I interferon production. P3-pDCs (PD-L1 – CD80 + ) adopted a dendritic morphology and adaptive immune functions. P2-pDCs (PD-L1 + CD80 + ) displayed both innate and adaptive functions. Each subpopulation expressed a specific coding- and long-noncoding-RNA signature and was stable after secondary stimulation. P1-pDCs were detected in samples from patients with lupus or psoriasis. pDC diversification was independent of cell divisions or preexisting heterogeneity within steady-state pDCs but was controlled by a TNF autocrine and/or paracrine communication loop. Our findings reveal a novel mechanism for diversity and division of labor in innate immune cells. Plasmacytoid dendritic cells (pDCs) are known for their copious IFN-I production. Soumelis and colleagues show that functionally and transcriptomically distinct human pDC populations can be generated from a single microbial or cytokine stimulus.